Rapid flow cytometry method for triploidy determination in turbot (Scopthalmus maximus L.) - Vázquez, Emilia; Fernández-Pato, Carlos; Martínez-Tapia, Concha; Blanco, Gloria; Sánchez Prado, José Antonio (2012)
Accurate methods for assessing triploidy are important because treatments designed to induce poliploidy are not 100% and offspring from treated eggs are usually a mixture of triploids and diploids. Flow cytometry was more recently applied to triploidy determination and usually carried out using erythrocytes. This paper describes a rapid and simple method for triploidy determination from the larval stage of turbot (Scopthalmus maximus) by flow cytometry. High-quality histograms were obtained from turbot larvae and the very good reproductibility provided unambigous discrimination of diploids and triploids even in early stages development. No